Pengaruh Kualitas Pelayanan Receptionist Terhadap Loyalitas Pelanggan Di Hotel Ibis Padang - Hani Harvisda (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Abstract.This research was used to see the effect of the quality of receptionist services on customer loyalty at the Ibis Hotel Padang. This type of research is descriptive quantitative with causal associative methods. The results of this study obtained data from a sample of 99 respondents who were guests at the Ibis Hotel Padang through a questionnaire using a Likert scale, then obtained the results of a simple linear regression test obtained F of 15,061 with sig. 0.000 <0.05, the receptionist service quality variable has an influence on customer loyalty variables by 13.4% and 86.6% influenced by other factors. Then obtained coefficient value of 0.369, meaning that each increase of 1 unit of service quality of receptionist will increase 37 units of customer loyalty to guests at Ibis Hotel Padang. Keywords: Service Quality, Customer Loyalty